Effects of jaw clenching on dynamic reactive balance task performance after 1-week of jaw clenching training - Fadillioglu, Cagla; Kanus, Lisa; Möhler, Felix; Ringhof, Steffen; Hellmann, Daniel; Stein, Thorsten (Frontiers in Neurology, 2023)
Introduction Good balance is essential for human daily life as it may help to improve the quality of life and reduce the risk of falls and associated injuries. The influence of jaw clenching on balance control has been shown under static and dynamic conditions. Nevertheless, it has not yet been investigated whether the effects are mainly associated with the dual-task situation or are caused by jaw clenching itself. Therefore, this study investigated the effects of jaw clenching on dynamic reactive balance task performance prior to and after 1 week of jaw clenching training. It was hypothesized that jaw clenching has stabilizing effects resulting in a better dynamic reactive balance performance, and these effects are not related to dual-task benefits. Methods A total of 48 physically active and healthy adults (20 women and 28 men) were distributed into three groups, one habitual control group (HAB) and two jaw clenching groups (JAW and INT) that had to clench their jaws during the balance tasks at T1 and T2. One of those two groups, the INT group, additionally practiced the jaw clenching task for 1 week, making it familiar and implicit at T2. The HAB group did not receive any instruction regarding jaw clenching condition. Dynamic reactive balance was assessed using an oscillating platform perturbed in one of four directions in a randomized order. Kinematic and electromyographic (EMG) data were collected using a 3D motion capture system and a wireless EMG system, respectively. Dynamic reactive balance was operationalized by the damping ratio. Furthermore, the range of motion of the center of mass (CoM) in perturbation direction (RoMCoM_AP or RoMCoM_ML), as well as the velocity of CoM (VCoM) in 3D, were analyzed. The mean activity of the muscles relevant to the perturbation direction was calculated to investigate reflex activities. Results The results revealed that jaw clenching had no significant effects on dynamic reactive balance performance or CoM kinematics in any of these three groups, and the automation of jaw clenching in the INT group did not result in a significant change either. However, high learning effects, as revealed by the higher damping ratio values and lower VCoM at T2, were detected for the dynamic reactive balance task even without any deliberate balance training in the intervention phase. In the case of backward perturbation of the platform, the soleus activity in a short latency response phase increased for the JAW group, whereas it decreased for HAB and INT after the intervention. In the case of forward acceleration of the platform, JAW and INT showed a higher tibialis anterior muscle activity level in the medium latency response phase compared to HAB at T1. Discussion Based on these findings, it can be suggested that jaw clenching may lead to some changes in reflex activities. However, the effects are limited to anterior–posterior perturbations of the platform. Nevertheless, high learning effects may have overall overweighed the effects related to jaw clenching. Further studies with balance tasks leading to less learning effects are needed to understand the altered adaptations to a dynamic reactive balance task related to simultaneous jaw clenching. Analysis of muscle coordination (e.g., muscle synergies), instead of individual muscles, as well as other experimental designs in which the information from other sources are reduced (e.g., closed eyes), may also help to reveal jaw clenching effects.